Verb-particle constructions in Cognitive Linguistics perspective: Compositionality behind selected English phrasal verbs - Izabela Jarosz (LingBaW)
The developments in Cognitive Linguistics have made it possible to uncover multiple meanings of composite structures to the effect that more and more scholars have become interested in the issue of semantic relations in verb-particle constructions. With only a handful of those focusing on both elements of such constructions, many of them have directed their research towards the study of particles exclusively. The current paper aims to advance the study on phrasal verbs by offering a new outlook on their compositional nature. In order to achieve a desired aim, the principle of partial compositionality is adopted here. Hence, apart from focusing on both the verb and the particle, the senses that go beyond those comprising the composite parts receive considerable attention in this study. The phrasal verbs singled out for the purpose of the analysis include: get and take with selected spatial-orientational particles.